Identifying teachers' job satisfaction - Ariffin, Adlina; Hashim, Hamimah; Sueb, Rosilawati (2013)
In this 21st century teachers are playing greater roles and given bigger commitments in the profession. These increased responsibilities and higher expectations do take its toll on them especially when they feel that they have not been fairly commensurated. Job satisfaction is indeed most crucial not only in determining the faithfulness of an employee to an organisation but more importantly it is the main indicator of an individual's level of commitment and productivity in his or her profession. This study aims to investigate the job satisfaction among private school teachers. The purposes of the study are to investigate the differences in job satisfaction among teachers with different years of teaching experience, to identify the relationship between years of teaching experience and job satisfaction, and to identify the differences between male and female teachers in job satisfaction. A quantitative approach which used a questionnaire, Teacher Job Satisfaction Questionnaire (TJSQ) developed by Lester (1982), was used a the main instrument to evaluate job satisfaction among teachers in a private school in Gombak district in Selangor. Thirty-two teachers became the participant in this research Overall, this research indicates that the teachers in the private school are generally satisfied with the profession.